6 If \( \cos \theta=-\frac{5}{13} \) and \( \sin \theta>0 \), then \( \tan \theta \) is \( \begin{array}{llll}\text { 1) } \frac{5}{12} & \text { 2) }-\frac{5}{12} & \text { 3) } \frac{12}{5} & \text { 4) }-\frac{12}{5}\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \( \tan \theta \), we can use the identity \( \tan \theta = \frac{\sin \theta}{\cos \theta} \). We know \( \cos \theta = -\frac{5}{13} \). Since we are given that \( \sin \theta > 0 \), we are in the second quadrant where cosine is negative and sine is positive. First, we can use the Pythagorean identity \( \sin^2 \theta + \cos^2 \theta = 1 \): \[ \sin^2 \theta + \left( -\frac{5}{13} \right)^2 = 1 \] \[ \sin^2 \theta + \frac{25}{169} = 1 \] \[ \sin^2 \theta = 1 - \frac{25}{169} = \frac{169 - 25}{169} = \frac{144}{169} \] Taking the square root (and remembering that sine is positive in this quadrant), we find: \[ \sin \theta = \frac{12}{13} \] Now we can substitute \( \sin \theta \) and \( \cos \theta \) into the tangent formula: \[ \tan \theta = \frac{\sin \theta}{\cos \theta} = \frac{\frac{12}{13}}{-\frac{5}{13}} = \frac{12}{-5} = -\frac{12}{5} \] Thus, the answer is: \(-\frac{12}{5}\). The correct option is \( \text{4) } -\frac{12}{5} \).